An unladylike profession : American women war correspondents in World War I - Dubbs, Chris (Military historian) (Potomac Books, an imprint of the University of Nebraska Press, 2020)
"Chris Dubbs tells the dramatic stories of more than thirty women who traveled to Europe to write about World War I for America's newspapers and magazines"--